Specificities of care to the adolescent crack user assisted in the psychosocial care network - Juliane Portella Ribeiro; Giovana Calcagno Gomes; Elitiele Ortiz dos Santos; Leandro Barbosa de Pinho (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: to analyze the specificities of care to the adolescent crack user assisted in the Network of Psychosocial Attention. Method: exploratory and descriptive study with qualitative approach. The participants were 20 professionals from the Center for Psychosocial Alcohol and Drug Attention and 10 professionals from the Center for Psychosocial Child and Adolescent Care. Data collection took place through semi-structured interviews and the data were processed by Nvivo 11 software and submitted to thematic analysis. Results: the care to the adolescent crack user assisted in the network involves care specificities in three scopes: adolescence as the life cycle stage, social aspects that involve the adolescent in the use situation, and differentiated care strategies to the adolescent using crack. Conclusion: the network services accessed by the adolescent crack user should be prepared to welcome him in their specificities, assessing the needs of care and promoting therapeutic workshops geared to the needs of this public in the specialized service. Implications for practice: the study may re-signify the care practices focused on the adolescent's needs. In addition, it is necessary to promote the strengthening of these services in the network with a view to subsidizing comprehensive and resolutive care.